Postmarketing Surveillance of Full Spectrum Hemp Extract CBD Products: Reported Adverse Events and Serious Adverse Events - Colleen M. Kingsbury; Ivori Zvorsky; Kevin Spelman (Drugs - Real World Outcomes)
Abstract Background There is a growing interest in products featuring hemp extracts and a demand for more data regarding their safety. To date, there is a paucity of published data on the safety of these products. Methods A retrospective analysis of postmarketing surveillance data collected in the United States on full spectrum hemp extract (FSHE) products manufactured by Charlotte’s Web (CW) was conducted over an 18-month period (January 2019 to July 2020). The frequency of adverse events (AEs) and serious adverse events (SAEs) was assessed by analyzing AE reports against the estimated number of consumers who purchased products and the total number of products sold. Results During the 18-month period, approximately 646,391 consumers purchased 1,939,172 products and 431 AEs were reported by 304 individuals. The estimated percentage of consumers who reported at least one adverse event was 0.05%. The percentage of AEs per products sold was 0.02%. Most AEs (98.14%) reported were Grade 1 (i.e., asymptomatic or causing mild symptoms), as classified by the Common Terminology Criteria for Adverse Events. Seven AEs were classified as serious, and the percentage of SAEs per products sold was 0.0004%. None of the reported SAEs were classified as a Grade 4 or Grade 5 (i.e., life threatening or fatal). Conclusions Approximately 0.05% of consumers who purchased the CW FSHE products from January 2019 to July 2020 reported an adverse event. The percentage of AEs and SAEs per products sold was 0.02% and 0.0004%, respectively. These data demonstrate that CW FSHE products appear to be well tolerated at recommended doses.